Establishing an effective legal framework for the growth of SMEs toward the African continental free trade - Shoko, Ropafadzo Sandra (Department of Commercial Law, 2026)
Small to medium enterprises (SMEs), especially those recently termed “startups,” are growing the economies of different countries worldwide, especially in Africa. SMEs can play a vital role in what the intra-Africa trade growth of the African Continental Free Trade Area (AfCFTA) aims for. One of the greatest problems hindering SMEs' growth is the absence of legal frameworks that adequately address their challenges. This study identified key challenges faced by SMEs and explored how to enhance the current SME legal frameworks to help SMEs tackle these challenges effectively. In answering the research question, “What would constitute an effective legal framework to assist the growth of SMEs towards the AfCFTA?” it explored the current SME legal landscape through a comparative desktop analysis of three countries: Kenya, Nigeria, and Tunisia. It examined the general laws governing SMEs and explored the specific Start-Up Law Acts that have surged in these African countries. It also examined the regional response from AfCFTA through its protocols, the AU Strategy for SME/I Development in Africa, and the implementation plan. In drawing lessons, the study compared the responses in Africa with the European Union's reaction to its own SME strategy for sustainable and digital Europe. Provisions on innovative financing, supporting a multistakeholder ecosystem, incentives that benefit the whole ecosystem, including investors, and action-oriented intellectual property protection and commercialisation measures are among the provisions identified as essential to constitute an effective SME legal framework. Furthermore, the study advocates that the intentionality and comprehensive benefits displayed in StartUp Acts should be incorporated into all SME legal frameworks to cater to conventional SMEs, especially considering that the environment enabling the full adoption of technology is not yet optimum. The research employed doctrinal research, which limited the information to the opinion and evidence of what other researchers had gathered. Empirical research would be valuable for future research to get a clearer perspective on what could constitute an effective SME legal framework.